PILATES MODALITY AND WELL-BEING: A COMPARATIVE EVALUATION OF SOCIO-DEMOGRAPHIC AND QUALITY OF LIFE INDICATORS IN WOMEN - Purenović-Ivanović, Tijana; Živković, Danijela; Đošić, Anđela; Filipović, Milica (Physical Education and Sport Through The Centuries, 2025)
Due to the everyday life stress, many individuals seek to enhance their quality of life (QoL) through physical activities that engage the whole body. Among the increasingly available techniques, the Pilates method stands out as a therapeutic and preventive model with the potential to improve QoL. The aim of this study was to examine and compare socio-demographic characteristics and QoL of women practicing Mat Pilates (MP, n=38) and Reformer Pilates (RP, n=38), aged 21–67. The analyzed baseline characteristics included age, anthropometric indicators (body height, body mass, BMI), age at menarche and menopause, duration of a single training session, and perceived exertion according to Borg’s scale. Additionally, socio-demographic factors (education level, employment, marital and living status, number of children, menstrual status, use of tobacco, alcohol or illicit substances) and Pilates-related variables (training frequency and length of practice) were collected. QoL was assessed using the WHOQOL-BREF questionnaire, which evaluates four domains—physical health, psychological health, social relationships, and environment—as well as overall perception of QoL and general health. The data were analyzed (descriptive statistics, Kolmogorov-Smirnov test, Mann Whitney U test) using SPSS 26.0. The obtained results showed statistically significant between-group differences (p>0.05) only in participants’ age and perceived exertion. Nevertheless, RP participants showed slightly higher QoL scores in the physical health domain (16.48±1.90 vs. 15.93±1.94), environment domain (14.33±2.30 vs. 14.09±1.96), and overall perceptions of QoL and general health (15.42±2.54 vs. 15.05±2.36). MP participants, however, scored marginally higher in psychological health (15.75±1.96 vs. 15.32±2.73) and social relationships (15.33±2.03 vs. 15.19±2.85). Overall, both groups expressed satisfaction with their QoL, with the highest levels noted in the physical health domain and the lowest in the environment domain, which encompasses financial resources, safety, health and social care, home environment, transport, etc. These findings across socio-demographic factors and QoL domains suggest that both forms of Pilates are equally accessible and beneficial forms of mind–body training among adult women.